Structure of a VirD4 coupling protein bound to a VirB type IV secretion machinery. (18th September 2017) - Redzej, Adam; Ukleja, Marta; Connery, Sarah; Trokter, Martina; Felisberto‐Rodrigues, Catarina; Cryar, Adam; Thalassinos, Konstantinos; Hayward, Richard D; Orlova, Elena V; Waksman, Gabriel
Abstract: Type IV secretion (T4S) systems are versatile bacterial secretion systems mediating transport of protein and/or DNA. T4S systems are generally composed of 11 VirB proteins and 1 VirD protein (VirD4). The VirB1‐11 proteins assemble to form a secretion machinery and a pilus while the VirD4 protein is responsible for substrate recruitment. The structure of VirD4 in isolation is known; however, its structure bound to the VirB1‐11 apparatus has not been determined. Here, we purify a T4S system with VirD4 bound, define the biochemical requirements for complex formation and describe the protein–protein interaction network in which VirD4 is involved. We also solve the structure of this complex by negative stain electron microscopy, demonstrating that two copies of VirD4 dimers locate on both sides of the apparatus, in between the VirB4 ATPases. Given the central role of VirD4 in type IV secretion, our study provides mechanistic insights on a process that mediates the dangerous spread of antibiotic resistance genes among bacterial populations. Synopsis: Multimeric ATPase VirD4 regulates substrate recruitment and transport in conjugative Type IV Secretion (T4S) systems, thereby contributing to the spread of antibiotic resistance genes. This study reveals the position of VirD4 within the inner membrane complex of the 12‐component T4S machinery. Purification of a functional T4S complex containing the eight VirB3‐10 proteins bound to the VirD4 protein. Dimers of VirD4 associate with the purified T4S complex. Systematic deletion of T4S system inner membrane complex (IMC) components shows that VirB10 controls VirD4 location in the complex. Negative‐stain electron microscopy structure shows the location of two copies of VirD4 within the T4S machinery. Abstract : Biochemical analysis and negative‐stain electron microscopy reveal the localisation of the VirD4 ATPase within the inner membrane complex of the Escherichia coli type IV secretion system.